Investigation of Standalone Solar Photovoltaic Water Pumping System With Reduced Switch Multilevel Inverter - Poompavai, T.; Kowsalya, M. (Frontiers in Energy Research, 2020)
Solar photovoltaic-powered water pumping systems are becoming very successful in regions where there is no opportunity for connecting the electric grid. The photovoltaic technology converts solar energy into electrical energy for operating direct current (DC) or alternating current (AC) motor-based water pump. In the case of a solar AC motor water pump, it engages two energy conversion stages (DC–DC and DC–AC) in the power conditioning unit. This usually resulted in increased size, cost, and complexity and decreases the efficiency of the entire system. The existing two-level inverter (DC–AC) stage generates higher harmonics in output voltage and higher electromagnetic interference that deteriorates directly the AC motor performance. Therefore, as a solution to the addressed problems, in this study, an innovative seven-level inverter with five power semiconductor switches for the operation of 0.5 HP single-phase induction motor pump had been investigated. The proposed multilevel inverter has the capability of providing lesser harmonic voltage that reduces filter requirements; along with this, other part components are used lesser when compared to other conventional multilevel inverters. To provide better insight into the work performance of this proposed topology, the simulation is executed in the MATLAB/Simulink environment, and hardware implementation of the same is depicted. From the results, it is observed that the proposed multilevel inverter topology obtained a total power loss of 1.6034 W and efficiency at 98.11%. This quality output voltage acquired from the multilevel inverter had been fed to drive the induction motor water pump; it pumped the water at the desired flow rate accordingly.